INTERDISCIPLINARY INTEGRATION OF ENVIRONMENTAL SAFETY CULTURE DEVELOPMENT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the article, the factors contributing to active mental activity in the process of integration of educational subjects of the formation of environmental safety culture in students - the appropriate combination of subjects for integration, the selection of methods, taking into account the actions of the teacher and students, are logically sequential, consistent, and scientifically described.